What is the Most Representative Standard Driving Cycle to Estimate Diesel Emissions of a Light Commercial Vehicle?. Issue 5 (2018) - Chindamo, Daniel; Gadola, Marco
Abstract: The paper presents a comparison between the emission levels produced along the most used standard driving cycles (NEDC, WLTC, CADC) by a Light Commercial Vehicle (LCV). A proven simulation tool based on real-world emission data (RDE, Real Driving Emissions) has been used instead of a demanding test campaign. Emission levels have been computed for each cycle in three conditions (urban, combined, extra-urban/highway). Then the results have been compared with Euro 5 limits and real-world emission levels to highlight each driving cycle objectivity and representativeness. Among others, the WLTC driving cycle seems to be the most plausible one yet, as expected, it is not very representative of the real world.